Diallyl Disulfide (DADS) Ameliorates Intestinal Candida albicans Infection by Modulating the Gut microbiota and Metabolites and Providing Intestinal Protection in Mice - Hu, Wanchao; Huang, Liou; Zhou, Ziyang; Yin, Liping; Tang, Jianguo (Frontiers in Cellular and Infection Microbiology, 2022)
Diallyl disulfide (DADS), a garlic extract also known as allicin, has been reported to have numerous biological activities, including anticancer, antifungal, and inflammation-inhibiting activities, among others. Although many studies have assessed whether DADS can treat Candida albicans infection in vitro, its in vivo function and the underlying mechanism are still not clear. Accumulated evidence has implicated the gut microbiota as an important factor in the colonization and invasion of C. albicans. Thus, this study aimed to identify the mechanism by which DADS ameliorates dextran sulfate (DSS)-induced intestinal C. albicans infection based on the systematic analysis of the gut microbiota and metabolomics in mice. Here, we determined the body weight, survival, colon length, histological score, and inflammatory cytokine levels in the serum and intestines of experimental mice. Fecal samples were collected for gut microbiota and metabolite analysis by 16S rRNA gene sequencing and LC–MS metabolomics, respectively. DADS significantly alleviated DSS-induced intestinal C. albicans infection and altered the gut microbial community structure and metabolic profile in the mice. The abundances of some pathogenic bacteria, such as Proteobacteria, Escherichia–Shigella, and Streptococcus, were notably decreased after treatment with DADS. In contrast, SCFA-producing bacteria, namely, Ruminiclostridium, Oscillibacter, and Ruminococcaceae_UCG−013, greatly increased in number. The perturbance of metabolites in infectious mice was improved by DADS, with increases in secondary bile acids, arachidonic acid, indoles and their derivatives, which were highly related to the multiple differentially altered metabolic pathways, namely, bile secretion, arachidonic acid metabolism, and tryptophan metabolism. This study indicated that DADS could modulate gut microbiota and metabolites and protect the gut barrier to alleviate DSS-induced intestinal C. albicans infection in mice. Moreover, this work might also provide novel insight into the treatment of C. albicans infection using DADS.